Investigating Japanese EFL learners’ communication apprehension and oral presentation strategies - Kamata, Akiko; Ariffin, Kamisah; Abdul Aziz, Roslina; Abas, Nadhratunnaim; Ahmad, Badli Esham; Okada, Hiroki (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines communication apprehension (CA) and oral presentation strategies among Japanese English as a foreign language (EFL) learner to understand their impact on verbal communication challenges. Despite educational reforms prioritizing communicative competence, Japanese learners face persistent difficulties, particularly in formal contexts like public speaking. A descriptive quantitative design was employed, and a purposive sampling method was used to select a sample of 140 EFL learners from a private Japanese university. Data was collected using the oral presentation strategies inventory (OPSI) and the personal report of communication apprehension (PRCA). Quantitative analysis via SPSS 29 assessed learners’ apprehension levels and strategy use patterns. Findings revealed moderate CA levels, with interpersonal communication inducing the most anxiety and public speaking causing the least. Learners relied heavily on message reduction and alteration (MRA) strategies, simplifying expressions to manage anxiety, while non-verbal (NV) strategies were minimally utilized. Positive correlations between strategy use and CA highlight the potential of targeted strategies to mitigate apprehension. Practical implications include the need to integrate Japanese cultural values into pedagogy to manage CA through collaborative learning, peer assistance, and structured oral activities, while also balancing accuracy with fluency and utilizing technological tools to support language development.